Identity, language and communication concerns of subcultures: The case of Antalya Cretans - Pınar ŞİMŞEK (PLoS ONE, 2025)
In today’s world, there is almost no homogeneous culture without interaction, and multiculturalism has become the most important phenomenon for all societies. Therefore, this cultural diversity, consisting of differences in culture, language, identity, religion, etc. has also brought along many problems. In the United Nations Educational, Scientific and Cultural Organization’s in “Convention for the Safeguarding of Intangible Cultural Heritage”, it is stated that identifying, documenting and surveying intangible cultural heritage of communities contributes to social harmony and tolerance. This research has been conducted on the identity, language, and communication of the Cretan in Türkiye. The purpose of the study is to contribute to social peace and tolerance by examining the identity, language, and communication perceptions and concerns of the Crete-origin community living in Türkiye as a subculture group, within the context of multiculturalism and intercultural communication. In this direction, preliminary interviews, observations and semi-structured in-depth interviews were made in the fieldwork carried out between May-July 2024 in the of the Cretan immigrants who have migrated and settled in Antalya at the first settlements one of the world cities with intense multiculturalism. In the study, an answer has been sought to the question “What are the identity and linguistic anxiety, harmony and conflict situations in the communication and interaction of Cretans living in Turkey as a subculture with the dominant culture?”. The findings were subjected to thematic and descriptive analysis and interpreted. It is predicted that the findings and results of this research can be used to contribute to studies aimed at preventing identity, linguistic and cultural incompatibility and possible conflicts caused by increasing migration movements.